Analysis of spermiogenesis like a tool in the study of the triatomines of the Brasiliensis subcomplex - Alevi, Kaio Cesar Chaboli [UNESP]; Mendonça, Priscila Pasqüetto [UNESP]; Pereira, Nathália Paiva [UNESP]; Fernandes, André Luiz Vieira Zorzetto; Rosa, João Aristeu da [UNESP]; Oliveira, Maria Tercília Vilela de Azeredo [UNESP] (Cellule MathDoc/Centre Mersenne, 2013)
The specific identification and systematic of triatomines have been based fundamentally on morphological observations. These organisms are classified into complexes and specific subcomplexes, principally for morphological parameters and geographical disposition. The use of cytogenetic analyzes has been represented as a tool in systematic and taxonomy of triatomines. Thus, the present work, through the analysis of spermiogenesis, aims to characterize this stage of spermatogenesis in triatomines little studied, and especially to compare it among the species Triatoma lenti and T. sherlocki, to assist in the diagnosis of differentiation of these insects. The presence of the heteropyknotic corpuscle is shown as a diagnostic tool to differentiate T. sherlocki and T. lenti, since it is absent in T. lenti. The analysis of the spermiogenesis in T. sherlocki also allowed us to address morphological differences between elongating cells, which were relatively smaller and more filamentous when compared to T lenti. Furthermore, the flagellum was observed in all stages of cell differentiation and elongation. This structure, which helps in the locomotion of the sperm, is hardly observed in cytogenetic analysis, especially throughout spermiogenesis. Thus, although other comparative approaches should be taken, this paper allowed emphasizing the analysis of spermiogenesis as an important cytotaxonomic tool that assists in the differentiation of morphologically related species, such as T. lenti and T. sherlocki. © 2013 Académie des sciences.
Keywords: Cytogenetics; Taxonomy; Triatominae; cytogenetics; insect; locomotion; morphology; sperm; taxonomy; animal experiment; cell differentiation; cell structure; flagellum; male; nonhuman; spermatogenesis; Triatoma; Triatoma lenti; Triatoma sherlocki; Animals; Brazil; Cytogenetic Analysis; Male; Species Specificity; Sperm Tail; Spermatids; Spermatogenesis; Hexapoda